GABA promotes peroxisome proliferation in Triticum monococcum leaves - Yunus Şahin; Taras Nazarov; Ercan Selçuk Ünlü; Andrei Smertenko; Nusret Zencrici (Plant Direct)
Abstract Although peroxisomes are integral for both primary and secondary metabolism, how developmental changes affect activity of peroxisomes remains poorly understood. Here, we used published RNA‐seq data to analyze the expression patterns of genes encoding 21 peroxisome metabolic pathways at successive developmental stages of Zea mays and Oryza sativa. Photorespiration was the most represented pathway in adult leaf relative to the juvenile stages. Components of reactive oxygen species (ROS)/reactive nitrogen species (RNS) metabolism, NADPH regeneration, and catabolism of polyamines were also enriched at later stages of leaf differentiation. The most commonly upregulated gene in differentiated leaves across all datasets of both species was BETAINE ALANINE DEHYDROGENASE (BADH). BADH functions in catabolism of polyamines where it converts 4‐aminobutyraldehyde (ABAL) to 4‐aminobutyrate (GABA). We tested the outcome of RNA‐seq analysis by qRT‐PCR in developing Triticum monococcum ssp. monococcum (Einkorn) seedlings. Consistent with the outcomes of RNA‐seq analysis, transcription of BADH and CATALASE3 (CAT3) were upregulated in older seedlings. CAT3 is an essential peroxisome biogenesis factor and a key enzyme of ROS homeostasis. Furthermore, exogenous application of GABA resulted in higher peroxisome abundance and transcriptional upregulation of BADH and a gene encoding another peroxisome biogenesis factor responsible for peroxisome fission, PEROXIN11C (PEX11C), in leaves. We propose that GABA contributes to regulation of peroxisome fission machinery during leaf differentiation.